Self-confidence and body image among adults engaged in daily bodybuilding exercise compared with non-exercising adults: a case-control study - Hayder Ameer Jabor; Bahaa Mirza Skal; Hasan Naeem Kareem; Richard Mottershead (Frontiers in Public Health, 2026)
Background Regular bodybuilding and resistance training may positively influence psychological wellbeing, particularly self-confidence and body image perception. This study aimed to compare self-confidence and body image between adults engaged in daily bodybuilding exercise and non-exercising adults in Iraq. Methods A case-control study was conducted in Al-Diwaniyah City, Iraq, between August 2025 and April 2026. A total of 188 participants were enrolled using a purposive sampling method, including 94 adults engaged in regular bodybuilding exercise and 94 non-exercising controls. Data were collected using a sociodemographic questionnaire, the Self-Confidence Scale, and the Body Image Scale. Data was analyzed using SPSS version 25. Statistical significance was considered at p < 0.05. Results No significant sociodemographic differences were observed between the two groups ( p > 0.05). Participants in the bodybuilding group demonstrated significantly higher total self-confidence scores compared with controls (148.37 ± 25.6 vs. 137.32 ± 26.7, p = 0.004). Significant differences were observed in several self-confidence domains, including social interaction, optimism, communication confidence, and appearance-related concerns (all p < 0.05). Body image scores were also significantly higher among bodybuilders (32.69 ± 7.6 vs. 29.70 ± 5.5, p = 0.002), indicating more positive body image perception and lower appearance-related distress. Logistic regression analysis showed that higher self-confidence scores were independently associated with increased likelihood of belonging to the bodybuilding group (OR = 0.988, 95% CI: 0.976–0.999, p = 0.040). Similarly, body image scores were significant predictors of group membership (OR = 0.937, 95% CI: 0.892–0.984, p = 0.009). Conclusion Adults who regularly participated in bodybuilding had significantly higher self-confidence and a more positive body image than non-exercising adults. These findings indicate an association rather than a causal relationship, as individuals with higher self-confidence and a more positive body image may be more likely to engage in bodybuilding. Regular participation in bodybuilding was associated with higher self-confidence and more positive body image among adults in this study. However, because of the case-control design, the direction of this association cannot be determined.